En jämförande studie av kalvuppfödningen på KRAV-anslutna och konventionella mjölkgårdar - Lindgren, Emma (2006)
In order to investigate if the KRAV-regulations have any effects on the health and welfare of calves, KRAV-affiliated farms were compared to conventional farms with respect to calf management and outcome. The dairy calf has had a low economical impact during history. Even today the value of the calf is low and a lot of calves have a poor health status. The calf breeding is built on tradition and on the fact, that cheap antibiotics have made it possible to ignore, the recommendations about good hygiene in the calf's environment. KRAV which started 1985 is the Swedish organisation that stipulates rules for organic farming.